Pengembangan E-modul Interaktif Berbasis Android dan Nature of Science Pada Materi Ikatan Kimia dan Gaya Antar Molekul Untuk Menumbuhkan Literasi Sains Siswa - Accraf, Lalu Bhabiet Rinjani; Suryati, Suryati; Khery, Yusran (IKIP Mataram, 2018)
Chemical bond sand intermolecular forces have abstract characteristics. Thepresence of technology in learning media can help students understand theconcept. The learning media in question can be in the form of an androidbasedinteractive e-module that provides convenient accessibility for users. Topresent the atmosphere of science learning, the e-module can be structuredwith the orientation of the Nature Of Science. This research and developmentaims to produce an android-based interactive e-module prototype with thenature of science oriented on chemical bonding and intermolecular forcessubject material to foster students' scientific literacy. This type of researchand development study was carried out with the Nieven development modelwhich consisted of 4 stages: (1) preliminary research stage, (2) prototypingstage ,(3) summative evaluation stage, and (4) systematic reflection anddocumentation stage. However, due to limited resources, this study wascarried out until summative evaluation. With the presentation formula andwith the categories, the results of expert validation obtained an averagepresentation of 90% with very feasible categories, and practical test resultson chemistry teachers obtained avalue of 95% with very feasible categoriesand the results of limited group trials obtained 85% with very decentcategory. Therefore, it can be concluded that the interactive e-moduleprototype that developed is very feasible and can be proceed to abroaderstage in fostering students' literacy skills.